THE EFFECT OF NUMBERED HEAD TOGETHER (NHT) INTEGRATED PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON IMPROVING CRITICAL THINKING AND STUDENT LEARNING OUTCOMES IN CLASS X ECOSYSTEM MATERIALS SMA NEGERI 11 AMBON AND SMA NEGERI 13 AMBON - Dwilestari, Desi Armawati; Smith, Alwi; Rehena, Johanis Fritzgal (Universitas Pattimura, 2021)
PBL and NHT learning models that have been integrated by this researcher are an amalgamation of the two learning models to help students develop a deep understanding of systematic knowledge simultaneously and train their critical thinking skills. This study aims to determine the effect of the integrated Numbered Heads Together (NHT) Problem-based learning (PBL) learning model on improving critical thinking and student learning outcomes. The type of research used is quantitative analysis research. The population of this study were all students of class X SMA Negeri 11 Ambon and all students of class X SMA Negeri 13 Ambon. The sampling technique used was random. Data analysis using simple linear regression test. The results of the regression analysis showed that there was a significant influence between the NHT-integrated PBL learning model on critical thinking and learning outcomes. The magnitude of the influence of the NHT Integrity PBL model on critical thinking is 81.1% and student learning outcomes are 61.7%. Whereas in SMA N.13 Ambon the magnitude of the influence of the NHT Integrity PBL model on critical thinking was 55% and student learning outcomes were 79.5%. Conclusion. There is a significant influence of the NHT integrated PBL learning model on critical thinking, namely 0.001 in SMA N. 11 and 0.040 in SMA N.13 Ambon, there is a significant influence of the NHT integrated PBL learning model on learning outcomes, namely 0.001 in SMA N. 11 and 0.002 in SMA N.13 Ambon.